The Akt Pathway Is Involved in Rapid Ischemic Tolerance in Focal Ischemia in Rats - Gao, Xuwen; Zhang, Hanfeng; Steinberg, Gary; Zhao, Heng (Translational stroke research, 2010)
Although the protective mechanisms of delayed ischemic preconditioning have received extensive studies, few have addressed the mechanisms associated with rapid ischemic preconditioning. We investigated whether ischemic tolerance induced by rapid preconditioning is regulated by the Akt survival signaling pathway. Stroke was generated by permanent occlusion of the left distal middle cerebral artery plus 30 min or 1 h occlusion of the bilateral common carotid artery (CCA) in male rats. Rapid preconditioning performed 1 h before stroke onset reduced infarct size by 69% in rats with 30 min CCA occlusion, but by only 19% with 1 h occlusion. After control ischemia with 30 min CCA occlusion, Western blot showed that P-Akt was transiently increased while Akt kinase assay showed that Akt activity was decreased. Although preconditioning did not change P-Akt levels at 1 and 5 h compared with control ischemia, it attenuated reduction in Akt activity at 5 h in the penumbra. However, preconditioning did not change the levels of P-PDK1, P-PTEN, and P-GSK3β in the Akt pathway, all of which were decreased after stroke. At last, the PI3K kinase inhibitor, LY294002, completely reversed the protection from ischemic preconditioning. In conclusion, Akt contributes to the protection of rapid preconditioning against stroke.